2020
DOI: 10.1111/1556-4029.14507
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Palatal Rugae Morphology Among Siblings*†

Abstract: Although there is clinical applicability of the palatal rugae as an identification tool in forensic odontology, controversy exists whether the palatal rugae patterns are stable or variable. The greater the genetic component, the higher the probability that palatal rugae patterns are stable. The aim of this study was to compare the palatal rugae morphology between full siblings and the proportion of variability due to genetic component. This cross‐sectional study was conducted on digital models of 162 siblings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Some studies have proposed differential functions, such as a population study in coastal Andhra [23]. One study revealed similarities between relatives, suggesting a certain heritability of palatine rugae patterns [24].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have proposed differential functions, such as a population study in coastal Andhra [23]. One study revealed similarities between relatives, suggesting a certain heritability of palatine rugae patterns [24].…”
Section: Discussionmentioning
confidence: 99%
“…All digital casts used in this study were selected from the archives [13]. The dental casts were scanned using a 3D light scanner, Rexcan CS+ scanner (Solutionix Corp.) [23].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, palatal rugae display a significant degree of individuality, with each person having a unique arrangement and pattern that distinguishes them from others [11]. In addition, evidence suggests a genetic association of palatal rugae among family members [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Korábbi publikációnkban sikerült bizonyítanunk, hogy egypetéjű ikreket a szájpadlásbordázat alapján 99,999%-os populációs lefedettséggel, 99%-os megbízhatósággal meg lehet különböztetni egymástól, digitális háromdimenziós mintákat használva, annak ellenére, hogy az ikerpár tagjai közel 100%-ban azonos genetikai állománnyal rendelkeznek (Simon et al 2020). A digitális összehasonlító módszer pedig a biometrikus azonosítást új alapokra helyezi, nem jár invazív beavatkozással, mintázatfelismerő szoftver segítségével költséghatékonyan, nagyfokú megbízhatósággal dolgozik, és ismert, hogy a fogak és a szájpadlásbordázat hosszú távon stabil, azonosításra alkalmas képletek (Azab et al 2016;Chong et al 2020;Kapali et al 1997;Kommalapati et al 2017;Limson-Julian 2004;Taneva et al 2017;Taneva et al 2015).…”
Section: Az Ikrek Szerepe a Biometrikus Azonosítás Fejlesztésébenunclassified